Congestion Control of Differentiated Services Networks by Sliding Mode Control - Barzamini, R.; Shafiee, M. (Elektronika ir Elektrotechnika, 2013)
In this paper sliding mode controllers (SMCs)’ techniques used and investigated for congestion control problem of differentiated Services (Diff-Serv) networks. Robustness against modelling uncertainties and disturbances are major feature of sliding mode controller. Chattering phenomenon affects sliding mode congestion control; to overcome this problem second order sliding mode control (SOSMC) is proposed as a congestion controller. There are three type of traffic in Diff-Serv networks; i.e. there are three types of queues and based in that, the quality of their services are categorized. Each of these types of traffic has its own congestion control mechanisms. Stability of each controller is proved by Lyapunov stability law. To evaluate the capabilities of our proposed robust control strategy, simulation results are provided for both sliding mode controllers and second order slide mode controllers and their corresponding efficiencies are compared. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.3264